(untitled) (Journal of National Institute of Ophthalmology, 2022)
Still, there is no ideal guideline for managing orbital lymphatic-venous malformations. Significant advances have been made in the treatment of lymphatic-venous malformation. Here, we attempt to review the current and recent evidence on management strategies, including sclerotherapy agents, systemic medications, and techniques. The orbital lymphatic-venous malformation is notorious for being very difficult to treat due to risks of morbidity, loss of vision and periocular disfigurement. Management depends on lymphangioma size, cyst type, and location. One option is carefully watching patients without doing any treatment (Observation). The option of surgery has typically been delayed until necessary because of the high recurrence rate, a high risk of morbidity because of injury to the globe, extraocular muscles, vessels, and optic nerve, and it is difficult to remove the entire lesion. Sclerotherapy is famous for reducing the size of orbital lymphangioma. Systemic medication can reduce the size and improve the clinical symptoms where the lesions are difficult to access surgically or with injections. These treatment modalities aim to reduce the size of the lesions, and cosmetic disfigurement and free from pain caused by these lesions, also avoid vision_threatening complications. J. Natl. Inst. Ophthalmol. 2022; 5(2):45-51